University governance in China and Japan: Major findings from national surveys. (November 2018) - Huang, Futao
Highlights: The university governance in China is characterized by a top-down style. Japan is concerned with a bottom-up one and its academics enjoy greater autonomy. The formation of university governance is context-based. Abstract: This paper identifies the main characteristics of the governance styles of four-year universities in China and Japan, based on findings from a cross-national academic survey conducted using a common questionnaire in 2011–2012. The study reveals that, although changes have occurred in the governance arrangements of universities in both countries under the influence of the new public management, entrepreneurialism, and other factors, the two case studies suggest while reforms in each country share some features in common with many systems, the two national systems embody two distinctive patterns of governance. From an international and comparative perspective, China is more characterized by a top-down style while Japan is more concerned with a bottom-up one. In contrast with Japan, the basic character of governance style in China has not been fundamentally changed. Neither the common nor the specific issues concerning governance of higher education in the two countries can be satisfactorily explained simply in terms of the numerical expansion of higher education enrollment as discussed by Trow, or other generic notions in the research literature. Rather, the specificities of each country, and the differences between them, must be explained in terms of the academic origins, traditions, cultural values, and especially the current political and social systems of China and Japan.